2010
DOI: 10.1007/s10059-010-0052-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of TNFSF7 (CD70) by DNA Methylation during Progression to Breast Cancer

Abstract: To escape the immune system, tumor cells may remove surface molecules such as the major histocompatibility complex (MHC) and co-stimulatory molecules, which are essential for recognition by lymphocytes. Down-regulation of the co-stimulatory molecules CD70 (TNFSF7) and CD80 may contribute to tumor cell survival; however, the mechanism of down-regulation of the TNFSF7 gene during tumorigenesis is poorly understood. Here we present evidence indicating that TNFSF7 gene expression is epigenetically down-regulated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Furthermore, the presence of a mutated p53 in this cell line, could account for the activation of the extrinsic apoptotic pathway and for its in vitro reduced sensitivity to SAHA. Recent studies reported that re-expression of CD70 in tumor cells may induce an anti-tumor response by T-lymphocytes and that the epigenetic downregulation of CD70 receptor by DNA hypermethylation is a strategy of breast cancer cells to escape immune response (32). Our observation that SAHA-induced histone hyperacetylation determines also an overexpression of CD70 and CD27 in MDA-MB-231 cells, supports the idea that SAHA treatment could restore an immune response against cancer cells.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the presence of a mutated p53 in this cell line, could account for the activation of the extrinsic apoptotic pathway and for its in vitro reduced sensitivity to SAHA. Recent studies reported that re-expression of CD70 in tumor cells may induce an anti-tumor response by T-lymphocytes and that the epigenetic downregulation of CD70 receptor by DNA hypermethylation is a strategy of breast cancer cells to escape immune response (32). Our observation that SAHA-induced histone hyperacetylation determines also an overexpression of CD70 and CD27 in MDA-MB-231 cells, supports the idea that SAHA treatment could restore an immune response against cancer cells.…”
Section: Discussionsupporting
confidence: 85%
“…Using the same methylation-specific PCR protocol described by Yu and colleagues (33), no hypomethylation of the CD70 promoter was seen in ccRCC tissues, which strongly expressed CD70 (data not shown). This suggests that the transcriptional regulation of CD70 is rather driven by HIF and does not depend on promoter hypomethylation in this tumor subtype.…”
Section: Discussionmentioning
confidence: 59%
“…4). TNFSF7 expression is epigenetically downregulated during progression in breast cancer cells (Yu et al, 2010) and it is also associated with the tumor necrosis factor (TNF) ligandreceptor death pathway (Hengartner, 2000). There are reports on apoptosis induction by TSNSF7-CD27L (Kashii et al, 1999) and TNFRSF9-TNFSF9 (Seko et al, 2004;Ebmeyer et al, 2011) in tumor cells.…”
Section: Discussionmentioning
confidence: 99%